La Segunda Internacional y el problema nacional y colonial / Eduard Bernstein ... [et al.] - Bernstein, EduardBax, Ernest BelfortKautsky, KarlRenner, KarlCalwer, RichardBauer, Otto (1881-1938) Strasser, JosephPannekoek, Anton (Cuadernos de pasado y presente ; 73 ; 74)
Contiene: Vol. I / Eduard Bernstein, E. Belford Bax, Karl Kautsky, Karl Renner -- Vol. II / Richard Calwer, Karl Kautsky, Otto Bauer, Josef Strasser, Anton Pannekoek